Tax withholding by the remitter based on the example of the lump-sum corporate income tax (WHT) – selected issues - Kucia-Guściora, Beata; Piszel, Rafał (Review of European and Comparative Law, 2022)
This article deals with the role and responsibility of the remitter in corporate income tax with respect to the socalled “withholding tax” (WHT) levied on income earned by non-residents. The authors focused their considerations on establishing the relationship between the statutorily defined standard obligations of the remitter and the implemented activities of this entity in relation to WHT. The subject is important due to international aspects of taxation of cross-border income not only on the basis of Polish corporate income tax regulations, but also with double taxation treaties and exemptions in withholding tax implemented from EU directives in mind. The answer to the research questions posed included tax, fiscal and penal, as well as international and EU aspects. The research thesis is that the obligation to collect tax under the WHT constitutes for the remitter “sui generis” right to perform this collection, and does not have the character of an absolute obligation constituting its subjectivity as a remitter. The analysis of the legislation, case law and literature, through the application of the legal-dogmatic method, has shown that the failure of the tax remitter to collect the tax is not a barrier to the filing a tax refund or overpayment claim by the tax remitter, and in fact constitutes an active legitimacy. The findings of the article are of practical significance for non-residents from the EU and third countries (from outside the EU) obtaining so-called passive income in Poland.